Effect of Non-Performing Loans on the Financial Performance of Commercial Banks in Nigeria (American International Journal of Business and Management Studies, 2019)
The study examined the effect of Non-Performing Loans on the financial performance of commercial banks in Nigeria between the periods of 1985 to 2016. The study employed the multiple regression techniques to analyze data collated from the Central Bank of Nigeria (CBN) statistical bulletin and Nigeria Deposit Insurance Corporation (NDIC) publications for various years. The result of the study shows that Non-Performing Loans to Total Loans ratio (NPL/TLR) and Cash Reserve Ratio (CRR) had statistically negative significant effect on Return on Asset (ROA). These result shows that a high level of non-performing loans would reduce the financial performance of commercial banks in Nigeria. Consequently, the study recommends that the regulatory authorities in Nigeria should create and support an environment where commercial banks in Nigeria can have a strong risk management practices.